PEMILAHAN JENIS KAYU KAPUR SINTOK (DRYOBALANOPS OOCARPA V. SI.) DARI JENIS-JENIS KAYU KAPUR LAINNYA - Y I Mandang (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
Kapur sintok (Dryobalanops oocarpa V. SI.) is the lightest and also the lowest in durability among the nine wood species of kapur. It is there fore necessary to separate this wood species from the other members, but it is difficult to separate based on anatomical characters. A chemical spot test proved to be simple and applicable. Kapur sintok responded negatively to the aplication of 5 percent of ferric ammonium sulphate while the other eight species responded positively.